1987
DOI: 10.1143/jjap.26.39
|View full text |Cite
|
Sign up to set email alerts
|

Laser Stimulated Desorption from Compound Semiconductors, Dimerization Enhanced Phase Transition

Abstract: Laser stimulated desorption (LSD) of neutral particles has been investigated in compound semiconductors MX of GaN, GaP, GaAs and CdS. No effects of crystallographic orientations on the characteristics of LSD, desorption yields, mean kinetic energies, and speed ratios have been recognized among (111) and (100) orientations in GaP and GaAs. This fact suggests that LSD does not follow the unimolecular dissociation of locally excited surface bonds, but occurs via a bulky event involving a phase transtion. The thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Therefore, equation ( 16) can be applied for the present analysis. Also, since the maximum value of N(0, t) is less than 2Z h for the highest excitation intensity, we can use the approximated form of J of equation (19) to calculate the bond-rupture rate J (t). The result of J (t) for I ex = 0.9 MW cm −2 , at constant J 0 , is shown in figure 22(b).…”
Section: P-bond Rupture On Inp(110)-(1 × 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, equation ( 16) can be applied for the present analysis. Also, since the maximum value of N(0, t) is less than 2Z h for the highest excitation intensity, we can use the approximated form of J of equation (19) to calculate the bond-rupture rate J (t). The result of J (t) for I ex = 0.9 MW cm −2 , at constant J 0 , is shown in figure 22(b).…”
Section: P-bond Rupture On Inp(110)-(1 × 1)mentioning
confidence: 99%
“…On the other hand, laser-stimulated desorption (LSD) below the melt threshold was studied for several MX compound semiconductors. In these studies, it was shown that the monatomic and diatomic nonmetallic species are emitted as major products, together with monatomic metallic species [18,19]. The yields of these neutral species often show a highly superlinear dependence on the laser intensity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation